Pendampingan Pemanfaatan Limbah Serat Aren sebagai Inovasi Bahan Bakar Alternatif Briket di Desa Sukamaju - Muhammad Rifai; Novan Somantri; Nabila Syahrani; Arifin; Syauqi Ramadhan; Risma Sepia; Alif Khanda Wicaksana; Iwan Satriyo Nugroho (Politeknik Piksi Ganesha Indonesia, 2025)
Sukamaju Village, Sumedang, is an area that relies on the agricultural and home industry sectors for income, including the processing of aren starch. This production process generates fiber waste that is not optimally utilized and has the potential to pollute the environment. This Community Service Program (CSP) aims to educate and train the community in utilizing arenga fiber waste to create environmentally friendly briquettes called BARASKA (Sukamaju Fire Coal). The activities were carried out thru a participatory approach involving observation, education, technical training, and mentoring. The results show that arenga fiber waste can be processed into effective and efficient briquettes as an alternative fuel. This program also successfully raised public awareness and skills, opened up new business opportunities, and contributed to environmental management. Despite still facing constraints in production and marketing tools, this initiative shows great potential in building a circular economy and sustainable villages.